A unique heterologous fibrin sealant (HFS) as a candidate biological scaffold for mesenchymal stem cells in osteoporotic rats - Orsi, Patrícia Rodrigues [UNESP]; Landim-Alvarenga, Fernanda Cruz [UNESP]; Justulin, Luis Antônio [UNESP]; Kaneno, Ramon [UNESP]; De Assis Golim, Marjorie [UNESP]; Dos Santos, Daniela Carvalho [UNESP]; Creste, Camila Fernanda Zorzella [UNESP]; Oba, Eunice [UNESP]; Maia, Leandro [UNESP]; Barraviera, Benedito [UNESP]; Ferreira, Rui Seabra [UNESP] (Springer Nature, 2017)
Background: The injection of mesenchymal stem cells (MSCs) directly into the bone of osteoporotic (OP) patients for rapid recovery has been studied worldwide. Scaffolds associated with MSCs are used to maintain and avoid cell loss after application. A unique heterologous fibrin sealant (HFS) derived from snake venom was evaluated for the cytotoxicity of its main components and as a three-dimensional biological scaffold for MSCs to repair a critical femur defect in osteoporotic rats. Methods: The cytotoxicity of HFS was assessed using a 3-(4,5-dimethyl-2-Thiazolyl)-2,5-diphenyl-2H-Tetrazoliumbromide (MTT) assay and transmission electron microscopy. The cells were cultured, characterized by flow cytometry and differentiated into the osteogenic lineage. Two-month-old rats underwent ovariectomy to induce OP. After 3 months, a 5 mm critical bone defect was made in the distal end of the rat femurs and filled with HFS; HFS + MSCs; and HFS + MSCs D (differentiated into the osteogenic lineage) to evaluate the effects. An injury control group (injury and no treatment) and blank control group (no injury and no treatment) were also included. The animals were observed at days 14 and 28 by microtomographic (micro-CT) analyses, histologic and biochemical analysis, as well as scanning electron microscopy. Results: The results revealed that one of the compounds of HFS, the thrombin-like enzyme extracted from snake venom, had no cytotoxic effects on the MSCs. OP was successfully induced, as demonstrated by the significant differences in the levels of 17β-estradiol, Micro-CT analyses and alkaline phosphatase between the ovariectomized (OVX) and non-ovariectomized (NOVX) groups. The histological data revealed that at 14 days after surgery in both the OVX and NOVX animals, the HFS + CTMs and HFS + CTMsD showed a higher formation of bone cells at the site in relation to the control group (without treatment). Collagen formation was evidenced through bone neoformation in all treated and control groups. No morphological differences in the femurs of the NOVX and OVX animals were observed after the surgical procedure. Scanning electron microscopy (SEM) confirmed the histological analysis. Conclusions: The new HFS composed of two non-Toxic components for MSCs showed capacity to promote the recovery of the bone lesions in OVX and NOVX animals at 14 days after surgery. In addition, the HFS enabled the differentiation of MSCs into MSCs D in the group treated with HFS + MSCs. Using the MSCs and/or MSCs D together with this biopharmaceutical could potentially enable significant advances in the treatment of osteoporotic fractures. Future clinical trials will be necessary to confirm these results.
Keywords: Cytotoxicity; Fibrin sealant; Fibrinogen; Osteoporosis; Snake venom